Transoral robotic surgery vs transoral laser microsurgery for resection of supraglottic cancer: a pilot surgery. Issue 1 (28th November 2013) - Ansarin, Mohssen; Zorzi, Stefano; Massaro, Maria Angela; Tagliabue, Marta; Proh, Michele; Giugliano, Gioacchino; Calabrese, Luca; Chiesa, Fausto
Abstract Background Transoral laser microsurgery (TLM) is a mature approach to supraglottic cancer, while transoral robotic surgery (TORS) is emerging. The present study compared these approaches. Methods The first 10 patients (2002–2005) given TLM were compared with the first 10 (2007–2011) given TORS for cT1‐3 cN0‐cN2c supraglottic cancer. Results A feeding tube was used in four TLM and seven TORS patients. Margins were more often positive, but operating times shorter, in TORS. All 10 TORS patients are without evidence of disease, but only six TLM patients remain disease‐free after much longer follow‐up. TORS was considerably less uncomfortable and fatiguing for the surgeon. Conclusions TORS seems as safe and effective as TLM. Shorter TORS operating times are probably attributable to prior experience with TLM. For laryngeal exposure, length of tube placement and margin evaluability, TLM was superior; however, this may change as TORS develops and transoral robotic instruments are optimized. Copyright © 2013 John Wiley & Sons, Ltd.